THE EFFECT OF PROVINCIAL MINIMUM WAGES, INDUSTRIALIZATION, AND POPULATION GROWTH ON URBANIZATION IN INDONESIA - Ressa Dwiarti; Hijri Juliansyah; Ratna; Cut Putri Mellita Sari (LPPM Universitas Malikussaleh, 2026)
This study aims to analyze the influence of Provincial Minimum Wage, Industrialization, and Population Growth on Urbanization in Indonesia from 1992 to 2024. This study uses the Autoregressive Distributed Lag (ARDL) method to see the dynamic relationship between independent variables and dependent variables. The results show that Provincial Minimum Wage has a positive sign and is not significant in the short run, while in the long run, Provincial Minimum Wage has a positive and significant effect on urbanization in Indonesia. Industrialization has a negative sign and is not significant in the short run, as well as in the long, industrialization has a negative sign and is not significant. Population growth has a positive sign and is not significant in the short run, while in the long run it has a significant and positive effect on urbanization in Indonesia.